The Effectiveness of Marlaat's Cognitive Behavior Intervention and Group Treatment Based on Change Stages for Recovery and Relapse Prevention Rates in Male Heroin Crack Addicts - S Khodadust; M Oraki; M Dehestani; SH Bayat (Drug Control Headquarters, Research and Education Office, 2014)
Objective: The aim of this study was the Study of effectiveness of Marlaat's cognitive behavior intervention and group treatment based on change stages for recovery and relapse rates in male heroin crack addictions. Method: In a experimental research design, 45 men addictions, who were diagnosed as the dependence of the heroin crack on the basis of DSM-IV-TR criteria, were chosen after successfully detoxified. They were divided two experimental groups (30 participants) and a control group (15 participants) that have been selected by random sampling. The first experimental group was undergone group treatment based on change stages underwent 16 sessions of 1.5 hours, totally 24 hours and the second experimental groups who were undergone Marlaat's cognitive behavior intervention has been held 15 sessions of 2 hours, totally 24 hours. The control group were just received MMT without any psychotherapy. All participants were assessed by structured interview, urine test, before treatment, after treatment and after 3 months follow up. Results: Results showed that both psychotherapy treatments were affected on recovery and relapse rates. Conclusion: It seems that psychological problems and conflicts before addiction and after addiction could be caused for individuals' tendency to narcotics consumption. Therefore, applying of psychotherapy could be useful in relapse prevention.